Effects of plant growth promoting rhizobacteria (PGPR) and cover crops on seed germination and early establishment of field dodder (Cuscuta campestris Yunk.) and early establishment of field dodder (Cuscuta campestris Yunk.) - Sarić-Krsmanović, Marija M; Bozic, Dragana M; Radivojevic, Ljiljana M; Gajić Umiljendić, Jelena S; Santric, Ljiljana; Vrbničanin, Sava P (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2017)
Several bacterial cultures: Bacillus licheniformis (MO1), B. pumilus (MO2), and B. amyloliquefaciens (MO3), isolated from manure; B. megatherium ZP6 (MO4) isolated from maize rhizosphere; Azotobacter chroococcum Ps1 (MO5) and Pseudomonas fluorescens (MO6), were used to test the influence of plant growth promoting rhizobacteria (PGPR) on seed germination and germination rate of field dodder (Cuscuta campestris Yunk.). Also, to examine the effect of host seeds on germination and initial growth of seedlings of field dodder plants in the dark and under white light, the seeds of four host plants were used (watermelon, red clover, alfalfa and sugar beet). Germinated seeds were counted daily over a ten-day period and the length of seedlings was measured on the final day.The results show that treatments MO3, MO4 and MO6 had inhibitory effects (15%, 65% and 52%, respectively), while treatments MO1, MO2 and MO5 had stimulating effects (3%, 3% and 19%, respectively) on seed germination of field dodder. The data for host seeds show that light was a significant initial factor (83-95%, control 95%) for stimulating seed germination of field dodder plants, apart from host presence (73-79%, control 80%).
Keywords: PGPR; Seed germination; Cover crops; Field dodder